Carnivore Contact: A Species Fracture Zone Delineated Amongst Genetically Structured North American Marten Populations (Martes americana and Martes caurina) - Lucid, Michael; Cushman, Sam; Robinson, Lacy; Kortello, Andrea; Hausleitner, Doris; Mowat, Garth; Ehlers, Shannon; Gillespie, Sara; Svancara, Leona K.; Sullivan, Jack; Rankin, Andrew; Paetkau, David (Frontiers in Genetics, 2020)
North American martens are forest dependent, influenced by human activity, and climate vulnerable. They have long been managed and harvested throughout their range as the American marten (Martes americana). Recent work has expanded evidence for the original description of two species in North America — M. americana and the Pacific Coast marten, M. caurina — but the geographic boundary between these groups has not been described in detail. From 2010-2016 we deployed 734 multi-taxa winter bait stations across a 53,474 km2 study area spanning seven mountain ranges within the anticipated contact zone along the border of Canada and the United States. We collected marten hair samples and developed genotypes for 15 polymorphic microsatellite loci for 235 individuals, and 493 base-pair sequences of the mtDNA gene COI for 175 of those individuals. Both nuclear and mitochondrial genetic structure identified a sharp break across the Clark Fork Valley, United States with M. americana and M. caurina occurring north and south of the break respectively. We estimated global effective population size (Ne) for each mountain range, clinal genetic neighborhood sizes (NS), calculated observed (Ho) and expected (He) heterozygosity, fixation index (FST ), and clinal measures of allelic richness (Ar), Ho, and inbreeding coefficient (FIS). Despite substantial genetic structure, we detected hybridization along the fracture zone with both contemporary (nuclear DNA) and historic (mtDNA) gene flow. Marten populations in our study area are highly structured and the break across the fracture zone being the largest documented in North America (FST range 0.21-0.34, mean = 0.27). With the exception of the Coeur d’Alene Mountains, marten were well distributed across higher elevation portions of our sampling area. Clinal NS values were variable suggesting substantial heterogeneity in marten density and movement. For both M. americana and M. caurina, elevationaly dependent gene flow and high genetic population structure suggest that connectivity corridors will be important to ensuring long-term population persistence. Our study is an example of how a combination of global and clinal molecular data analyses can provide important information for natural resource management.